Navigating the geopolitical chessboard - Diduc, Sniazhana (Routledge, 2025)
ABSTRACT This chapter broadens the focus to include global power shifts and their impact on M&As. The author reframes mergers and acquisitions (M&As) as a strategic tool of geopolitical influence, extending beyond corporate growth and market expansion. The chapter argues that M&As enable nations to project soft power and advance geopolitical interests, particularly in critical sectors like technology, infrastructure, and energy. By examining global power shifts – such as the evolving roles of China, Russia, and the US – the chapter connects corporate strategy with state agendas. It explores regulatory scrutiny, state-owned enterprises, and political considerations shaping M&As. This perspective provides scholars and practitioners with a deeper understanding of M&As as a geopolitical instrument, with future research focusing on their long-term geopolitical impact and state intervention in cross-border deals.
Keywords: Power shift; Mergers and acquisitions; Human Resource Management; Henkilöstöjohtaminen